A PLEA OF DOUBLE JEOPARDY BY ACCUSED EMPLOYERS: ARE THERE LIMITS? - Fareed Moosa (Obiter, 2021)
The rule against double jeopardy entails that, generally, a person cannot be charged more than once for the same, or substantially the same, offence or misconduct in respect of which he or she has been convicted or acquitted. Under the Constitution of the Republic of South Africa, 1996, this rule is part of an accused’s right to a fair trial. This article shows that every employer prosecuted for allegedly not complying with either employees’ tax obligations in the Fourth Schedule of the Income Tax Act 58 of 1962, or for an offence at common law, is entitled to raise the procedural defence of double jeopardy. This article argues that the recent judgment in Grayston Technology Investment (Pty) Ltd v S is authority for the proposition that, in any such prosecution, an accused employer may invoke double jeopardy, even if the prior punishment or acquittal stems from non-criminal proceedings under the Tax Administration Act 28 of 2011 before the Tax Court or the Tax Board. A key hypothesis of this article is the argument that double jeopardy ought not to be applied as an inflexible procedural rule in every instance. This is because such an approach would lead to the undesirable result of undermining the Legislature’s objective in catering for criminal and civil sanctions in respect of certain violations of fiscal legislation. No hard-and-fast rules can be laid down in advance as to when double jeopardy may be successfully invoked. Each case needs to be decided on its own facts. It is contended that when a court decides whether to uphold a double-jeopardy defence, it must strike an equitable balance between, on the one hand, the accused employer’s fundamental right to a fair trial and, on the other, society’s legitimate interest in ensuring that taxpayers comply with their tax obligations on pain of adequate punishment for non-compliance.